Photocharacterization and pH Sensing Properties of a Novel Synthesized Fluorescent Schiff Base Derivative - Zurnacı, Merve (Karadeniz Fen Bilimleri Dergisi, 2025)
Design and synthesis of different, highly sensitive and fast response fluorescent materials are very important in the development of pH sensors. In this study, a new pH-sensitive Schiff-base ligand (PHS1) was synthesized by the condensation reaction of newly synthesized 1,3,4-thiadiazole derivative containing phenanthroimidazole (PHT1) with 3,5-ditertbutylsalicylaldehyde (1:1) in ethanol. The molecular structure was confirmed by structural characterization methods. The absorption and fluorescence properties of PHS1 were investigated in DMSO to determine the photocharacterization properties. Then, PHS1 was investigated as a fluorescent pH sensor. UV absorption and emission studies of PHS1 with varying pH (at pH=2.0, 4.0, 6.0, 8.0, 10.0 and 12.0) were determined in Britton-Robinson buffer. The absorption wavelength recorded at 345 nm at pH 2.0 showed bathochromic effect as pH increased (at pH= 4.0; 6.0 and 8.0). At pH 10.0 and 12.0, PHS1 showed two absorption peaks at 357 nm and a new low energy absorption band at 405 nm. The fluorescence spectrum of PHS1 showed a red shift with an increasing wavelength from 439 nm to 473 nm between pH=2.0 and 12.0. These results showed that PHS1 is sensitive to pH change in acidic and basic environments.